Microstructure evolution of austenitic stainless steels under high-cycle-fatigue loading at deep cryogenic temperature. (15th March 2023) - Xin, Jijun; Zhang, Hengcheng; Sun, Wenjun; Wang, Wei; Wu, Dong; Lyu, Bingkun; Shen, Fuzhi; Fang, Zhichun; Huang, Chuanjun; Li, Laifeng
Abstract: In this work, the microstructure evolution and magnetic properties of the 316LN austenitic stainless steels under high-cycle-fatigue loading at liquid helium temperature (4.2 K) were assessed by using the X-ray diffractometer (XRD), electron microscopy and magnetic measurements. The microstructure was composed of a single face-centered cubic (FCC) phase, and the high local misorientation was found near the grain boundaries. Observations through the high-resolution transmission electron microscopy reveals that the deformation was dominated by the dislocation and stacking faults. The magnetic susceptibility varies slightly after cyclic loading test at 4.2 K. Graphical abstract: Image, graphical abstract